Epidemiology of chronic pain in the office of a pain specialist neurologist - Karen dos Santos Ferreira; José Geraldo Speciali (Arquivos de Neuro-Psiquiatria)
Objective The objective of the present report was to describe the working experience of a pain specialist neurologist after concluding a medical residency program on neurology, area of concentration pain. Method A retrospective study was conducted for one year in the office of a pain specialist neurologist. Patients older than 18 years with chronic pain according to the criteria of the International Association for the Study of Pain, were included. Demographic data, chronic pain data and the treatments instituted were investigated. Results A total of 241 medical records were reviewed, mean patient age was 52.4 years and 79 (66.9%) were women, and the mean score on a numeric pain scale was 8.69. The diagnoses were headaches (74.6%), neuropathic pain (17%) and ostheomuscular pain (8.2%). We did not detect cancer pain. Patients received medication and procedures of anesthetic blockade. Conclusion This data can guide new medical residency programs on Neurology, area of concentration pain, to plan activities and studies.